Anchorage behavior of large shear reinforcements with anchor heads and 180-degree hooks. (October 2022) - Yuan, Lin-Lin; Yang, Yuan-Zhang; Sun, Bo-Chao; Zhao, Wei-Jian
Abstract: The use of headed bars in place of conventional hooked bars and closed stirrups can provide sufficient anchorage strength while solving the problems of rebar congestion and difficulties in construction, especially in seismic structures with large shear reinforcements. This paper conducted experimental and numerical studies to investigate the anchorage behaviors of shear reinforcements with anchor heads and 180-degree hooks. A total of 28 pull-out specimens were designed and tested. The specimens were classified into two groups based on the anchor types (180-degree hooks and friction welded anchor plates), and each group had seven nominal bar diameters. The test results show that compared with 180-degree hooked bars, the growth of the pull-out displacements of headed bars are effectively restrained, and the yielding pull-out displacements are reduced by 33%–75%. To gain a deeper understanding of anchorage mechanisms, finite element (FE) models of the specimens were established and validated. For shear reinforcements with anchored heads, the anchorage is mainly based on bearing effect. The tensile fracture of rebars is prior to the overall yielding of anchor heads and local crushing of concrete. For shear reinforcements with 180-degree hooks, to simulate the interaction condition between hooks and concrete, a highly refined rib-scale modeling method was proposed and compared with the existing bar-scale modeling method. The proposed rib-scale model can eliminate the reliance on the assumption of interfacial contact relationship and predict the anchorage behavior of hooks with discrepancies of less than 10%. The anchorage mechanism of the 180-degree hook is mainly based on bonding effect, supplemented by local bearing. When the stress of bar reached the yield strength and tensile strength, the local bearing stress accounted for 6.8% and 11.6% of the total stress, respectively.